Research on the Amplitude–Phase Motion Equation for the Modeling of Wind Power System - Liu, Qunying; Cai, Maojie; Jiang, Yazhou; Zhu, Deqing; Zheng, Runsheng; Chen, Shuheng; Zhang, Changhua (Frontiers in Energy Research, 2022)
The increasing penetration of wind power together with its high volatility could significantly impact the transient stability of the power grid. To quickly evaluate this impact, current engineering practice is primarily relying on time-domain simulation, which is computationally expensive despite that the results are more accurate. To solve this computational complexity issue, the amplitude–phase motion method is proposed to establish the electromechanical transient simulation model of the double-fed induction generator (DFIG) for wind energy. However, the traditional amplitude–phase motion equation (APME) suffers from the instability control from the abrupt change of terminal voltage induced by the system changes or flickers. To improve the transient stability of DFIG, this study firstly incorporates the q-axis current together with the amplitude change of terminal voltage into the phase error of the phase-locked loop (PLL). Then, the output phase of the terminal voltage of DFIG is highly combined with the q-axis current and the amplitude of terminal voltage to improve the internal control effect of the typical APME. The simulation results in the four-machine two-area power system with one wind farm demonstrate that the proposed method is able to maintain a stable operation of the wind farm and the power grid when experiencing a sharp disturbance of wind speed.